Management of Convergence Insufficiency and Oculomotor Dysfunction: A Neuro-Optometric Perspective. - Mani, Revathy; Reddy, Ashwini V. C.; Hussaindeen, Jameel Rizwana; S., Durga Priyadarshini (Optometry & Visual Performance, 2017)
Background: Sensory problems are common after traumatic brain injury, which can lead to the disruption of the visual process, causing eye problems such as difficulty with accommodative function, binocular fusion, and fixation ability. MRI findings are usually normal in mild traumatic brain injury (mTBI). However, these patients present with varying visual comorbidities. The injuries sustained are most often diffuse and are caused by shearing and stretching of the brain fibers, as well as the neurotoxic cascade induced by the injury. Management of such cases requires an interdisciplinary approach where optometrists play an important role in delivering primary eye care. This case report emphasizes the role of an optometrist in the diagnosis and management of mTBI-related vision disorders. Case Report: Mr. A, a 25-year-old gentleman, presented to the Neuro-Optometry Clinic (NOC) with a chief complaint of difficulty tracking words and of letters moving during reading. These symptoms began following a head injury due to a fall 6 months prior. He also complained of dizziness while moving his eyes and difficulty remembering the text he read. He was first examined in the Neuro-Ophthalmology clinic and was referred to the NOC for further evaluation. At NOC, he was diagnosed with convergence insufficiency, oculomotor dysfunction, and mild visual motion sensitivity. He underwent vision therapy for 10 sessions to train accommodation, vergence, and eye movements. His symptoms decreased, and the binocular vision parameters and reading speed improved from baseline. Conclusion: Neuro-Optometric Vision Therapy (NOVT) is an important treatment option to eliminate the visual symptoms and to improve the quality of life in patients with mTBI.